programa de educación cívica en la participación estudiantil durante las actividades comunitarias de estudiantes de la Institución Educativa Pública variante agropecuaria - IEPVA Taish comunidad nativa Cocha Purahua, río Huasaga, distrito de Andoas, provincia Datem del Marañon 2025 - Ramirez Tananta, Renzo Jesus (2026)
The objective: To verify the extent to which the Civic Education Program improves student participation in community activities among students at the IEPVA Taish public agricultural school in the native community of Cocha Purahua, on the Huasaga River in the district of Andoas, province of Datem del Marañon, 2025. Using a pre-experimental quantitative approach, with a single pre-test/post-test group in a population of 106, a sample of 39 students was extracted. In the descriptive analysis prior to the program, 97.4% of students had insufficient participation. After the program, the “Adequate” category reached 89.7%, reflecting a significant improvement in student involvement. At ∞ = Alpha = 0.05 = 5%, the test statistic was standardized Z with a Zc = -5.444, p-value = 0.000 = 0.0%, at an error level of 0.000%. Student participation in community activities improves in all its dimensions as a result of the civic education program in its dimensions: Commitment to community activities, Collaboration in community work, and Impact of community activities, thus approving the derived hypotheses. It is therefore concluded that, at a 95% confidence level, the research hypothesis is proven: The Civic Education Program significantly improves student participation in community activities.